2015
DOI: 10.1097/rlu.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

A General Cutoff Level Combined With Personalized Dynamic Change of Serum Carcinoembryonic Antigen Can Suggest Timely Use of FDG PET for Early Detection of Recurrent Colorectal Cancer

Abstract: A posttreatment CEA level rise to greater than 13 ng/mL is suggestive of the optimal use of FDG PET, and so is a mild increase below 13 ng/mL at an increase rate over 3.34.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…One was the definition of an “elevated” pCEA level. Because the elevation of preoperative pCEA was associated with the development of tumor stage, the traditional use of a single pCEA cutoff value for prognostic assessment may not be suitable for all CRC patients at other stages [ 11 13 ]. Many recent studies suggested the significance of using different cutoff values for prognostic evaluation [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One was the definition of an “elevated” pCEA level. Because the elevation of preoperative pCEA was associated with the development of tumor stage, the traditional use of a single pCEA cutoff value for prognostic assessment may not be suitable for all CRC patients at other stages [ 11 13 ]. Many recent studies suggested the significance of using different cutoff values for prognostic evaluation [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the FACS trial, recurrences were missed in patients who had experienced a gradual rise in CEA level, and it was suggested previously that this might be avoided by considering the trend in a series of results over time. In the CEAwatch trial, further investigation was based on CEA trend, on the basis of evidence from other studies that it provides better diagnostic yield than a single measurement.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report on interpreting CEA trend in order to initiate positron emission tomography scans to detect recurrence is based on very small numbers and does not report a comparable threshold. 36 Interestingly, in the context of our finding that a negative trend had diagnostic value, Ito et al 37 reported that a slow reduction in the CEA level following primary surgical treatment was predictive of recurrence (presumably residual disease) in the early period after primary surgery.…”
Section: -35mentioning
confidence: 72%